2022
DOI: 10.1177/25158414211063293
|View full text |Cite
|
Sign up to set email alerts
|

The impact of phacoemulsification surgery on vision-related quality of life in senile cataract patients

Abstract: Background: Phacoemulsification surgery may have beneficial effects on the quality of life of patients with senile cataract. These effects can be evaluated with the help of questionnaires and tests. Purpose: To evaluate the effect of the phacoemulsification surgery on the vision-related quality of life (VR-QOL) in patients with senile cataract using the 25-item National Eye Institute Visual Functioning Questionnaire (NEI-VFQ-25) and functional independence measure (FIM) tests. Methods: The data collection was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The systematic review identified several key risk factors associated with cataract development, including age, preoperative visual acuity, and comorbidities such as glaucoma and hypertension. 9,10,15 Consistent with previous findings, our case report patient presented with age-related cataract, emphasizing the age-related nature of this condition and the importance of regular ophthalmic screenings in the elderly population.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The systematic review identified several key risk factors associated with cataract development, including age, preoperative visual acuity, and comorbidities such as glaucoma and hypertension. 9,10,15 Consistent with previous findings, our case report patient presented with age-related cataract, emphasizing the age-related nature of this condition and the importance of regular ophthalmic screenings in the elderly population.…”
Section: Discussionsupporting
confidence: 91%
“…Akpolat, et al 10 (2022) phacoemulsification surgery significantly improves vision-related quality of life (VR-QOL) in patients with cataracts. The National Eye Institute Visual Functioning Questionnaire (NEI-VFQ-25) is a valid and reliable tool for measuring visual function post-ocular surgery.…”
Section: Thessaloniki Greecementioning
confidence: 99%
“…The National Eye Institute Visual Functioning Questionnaire-25 (NEI-VFQ-25) has been found to be a validated instrument for measuring vision-related QoL [9]. This 25-item questionnaire has been used to assess patients' QoL in a variety of eyerelated disorders [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Although the preoperative VA was signi cantly worse in the blindness prevention program group than in the conventional cataract surgery group, there was no signi cant difference in the preoperative VF-QOL questionnaire scores. Akpolat et al [34] reported that cataract patients with a higher education level had worse vision-related QOL than those with a lower education level, even if the baseline BCVA was similar. Munaw and Tegegn [35] reported that participants with high educational levels who are visually impaired are twice as likely to develop psychological distress than those who cannot read or write.…”
Section: Discussionmentioning
confidence: 99%